Regulatory rationalisation clauses in FTAs: A complete survey of the US, EU, and China - LIN, Ching-Fu (Institutional Knowledge at Singapore Management University, 2018)
Mechanisms on regulatory coherence or good regulatory practices have emerged as one of the unique features of preferential trade agreements (PTAs) in the age of mega-regionalism. Led by the United States, for instance, the Trans-Pacific Partnership (‘TPP’), now known as the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (‘CPTPP’) introduces a standalone chapter that focuses on the domestic rule-making process. Such design is unique for it goes beyond traditional output-oriented proxies by including a set of input-oriented elements that apply to the rulemaking process of each party, before a regulatory action is taken. These elements, like transparency, public consultation, regulatory impact assessment, inter-agency coordination and review, are in large part modelled on the American Administrative Procedure Act (‘APA’) and several executive orders with a view to ‘rationalising’ the administrative lawmaking process and to responding to the concerns about a regulatory state. For years, the US has been exporting this APA-style regulatory philosophy elsewhere: from the Organisation of Economic Co-operation and Development (‘OECD’) and the Asia-Pacific Economic Cooperation (‘APEC’) to trade negotiations to which it is a party, including the above-mentioned TPP and the Transatlantic Trade and Investment Partnership (‘TTIP’). Notwithstanding these efforts, however, there are hurdles for regulatory coherence to be further diffused as a new global norm since it goes beyond trade to involve complicated economic, social and political endowments of different trading partners. The role of another two major players, namely China and the European Union, is hence of particular significance in this context. This article seeks to sketch out the contour of the emerging regulatory coherence by mapping the trajectory of its historical development and offering a comprehensive survey of how China, European Union, and the United States have managed it across different contexts.